The role of the private sector in advancing democratic development : what works, what doesn't and why? - Thiam, Papa Demba (2007)
Argues that democractic development and private sector development are mutually supportive and contribute to shared growth and poverty reduction, but they need to be sustained by result oriented public-private partnership.